Characteristics and driving factors of power generation performance in microbial fuel cells: an analysis based on the CNKI database - Zhang, Ruikai; Dai, Wentao; Xiang, Hongyong; Chen, Jie; Yi, Ting; Li, Jiayi; Zhang, Jiebin; Yang, Qiuxi; Xiao, Rui; Li, Xiang (Frontiers in Microbiology, 2025)
Microbial fuel cells (MFCs) have become one of the most promising technologies in the field of ecology and environmental science due to their dual functions of power generation and pollutant removal. However, the generally low power generation performance of MFCs is one of the bottlenecks constraining their development, and numerous studies have focused on the improvement of power generation performance. The majority of previous empirical studies were based on single experimental data, which means there may be large differences in experimental conditions and settings, leading to various or even contradictory conclusions. In this study, we collected a total of 10,826 cases from 186 publications in the China National Knowledge Infrastructure Database to quantitatively and systematically investigate the general patterns and driving factors of power generation performance in MFCs. Our results showed that (1) the power density, voltage, and reaction duration were significantly lower (~25%) in this study, while the coulombic efficiency and ambient temperature were significantly higher (13.4–33.1%) than those reported in other meta-analyses or review papers; (2) reaction chamber volume and cathode surface area were stronger predictors for the majority of power generation performance indices than other device configuration indices, especially cathode chamber volume, which explained >70% of the variances in power density and coulombic efficiency; (3) ambient temperature, external resistance, and reaction duration had greater effects on power generation performance than other reaction conditions; and (4) substrates with pre-treatment, especially with biological treatment, showed 10–40% higher values for the majority of power generation performance indices compared to pre-treatment with physical and chemical methods, and solid substrates showed better power generation performance than liquid and fluid substrates for the majority of indices. Our results suggest that dual-chamber systems, larger cathode surface areas, neutral pH levels, ambient temperatures of 30–35°C, and biological pre-treatment of substrates may be helpful in improving the power generation performance of MFCs.